Palladium(0)-catalyzed efficient synthesis of allylic N- and S-benzoheterocycles linked to unsaturated carbohydrate derivatives - Ronaldo Nascimento de Oliveira; Wilson S. do Nascimento; Girliane R. da Silva; Tânia Maria S. Silva (Orbital: The Electronic Journal of Chemistry, 2012)
An efficient strategy was developed to envisage the synthesis of new N- and S-benzoheterocycles attached to the C-4 position of pseudo-carbohydrates. The reaction was performed with unsaturated carbohydrates and benzoheterocycles as nucleophiles in the presence of a catalytic amount of tetrakis(triphenylphosphine)palladium(0) and chelating bidentate ligand dppb. This strategy allowed easy access to benzoheterocyclic sugars in moderate-to-good yields. A preliminary study for antioxidant activities of O-glycosides 2,3-unsaturated was evaluated based on the 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging and 2,2-azinobis 3-ethylbenzothiozoline-6-sulfonic acid (ABTS) radical cation decolorization assay, and showed low-to-moderate activities.